The Influence of Green Marketing and Social Media Engagement on Purchase Decisions of The Body Shop Products among Consumers in Cirebon City - Amanda Putri Denika; Rahmadi (Indonesian Journal of Business Analytics, 2026)
Businesses are encouraged to implement sustainable and interactive marketing tactics by rising consumer knowledge of environmental issues and the intensity of social media use. The purpose of this study is to examine how social media engagement and green marketing affect Cirebon City customers' decisions to buy products from The Body Shop. This study employs a quantitative approach with a survey method, collecting data from 158 individuals chosen through purposive sampling procedures using a structured questionnaire. With the aid of SPSS software, multiple linear regression was used to examine the data. The study's findings demonstrate that green marketing significantly and favorably affects purchase decisions, suggesting that eco-friendly marketing techniques might boost consumer preferences and confidence. Additionally, Purchase Decisions are positively and significantly impacted by Social Media Engagement, highlighting the significance of customer involvement through social media in influencing purchase behavior. With a determination coefficient value of 75.6%, the two independent factors significantly influenced purchasing decisions at the same time. These results serve as the foundation for businesses to create more successful and customer engagement-focused marketing strategies, as well as an empirical contribution to the development of sustainable marketing and digital marketing studies.